Peran Guru Agama Islam dalam Pembinaan Akhlaq Remaja di Wilayah Majlis Ta'lim Al Munawwarah Cibubur - Sidiq Sekar Ihsan (SAP (Susunan Artikel Pendidikan), 2019)
The crime technology has been a threatening for the parents, however for all kind of aspects sophisticated tehnology development the teenagers are hopes for the family, the religion, the nation and the country.  The religion’s teachers have a big contribution when the teenagers have a bad morality, a perfunctory character and not royal to the parents. At present, Islamic’s teachers have a big contribution to lead the teenagers to be a good morality and character, therefore as an Islamic’s teachers are demanded to be a wise and to teach and to guide in creating their character. In this jurnal the writer has attempted to have an approach and an action to the teenagers in order to create a good expectation morality for the family, the religion, the nation and the country.  Based on the problems above the some methods have been applied by the writer, such as directing, tranning, habituation, interview and a goodly pattern for the teenagers. Those methods are important to train them into a good morality. The religion teachers are not only give the training but also some good actions to Allah SWT’s creatures for examples giving some charties to the orphaned and the poors. Likewise, the writer has applied the study case and library research to archieve the role of Islamic’s teacher in guidance teenagers’ morality so that, it is able to be a solution to the teachers and to reach a good morality’s performance in technology era and able to defend the family’s institution as a superior miniature society.